Exercise-induced asthma, respiratory and allergic disorders in elite athletes: epidemiology, mechanisms and diagnosis: Part I of the report from the Joint Task Force of the European Respiratory Society (ERS) and the European Academy of Allergy and Clinical Immunology (EAACI) in cooperation with GA(2)LEN - Carlsen, K H; Anderson, S D; Bjermer, Leif; Bonini, S; Brusasco, V; Canonica, W; Cummiskey, J; Delgado, L; Del Giacco, S R; Drobnic, F; Haahtela, T; Larsson, K; et al. (Allergy (Copenhagen), 2008)
Aims: To analyze the changes in the prevalence of asthma, bronchial hyperresponsiveness (BHR) and allergies in elite athletes over the past years, to review the specific pathogenetic features of these conditions and to make recommendations for their diagnosis. Mehtods: The Task Force reviewed present literature by searching Medline up to November 2006 for relevant papers by the search words: asthma, bronchial responsiveness, EIB, athletes and sports. Sign criteria were used to assess level of evidence and grades of recommendation. Results: The problems of sports-related asthma and allergy are outlined. Epidemiological evidence for an increased prevalence of asthma and BHR among competitive athletes, especially in endurance sports, is provided. The mechanisms for development of asthma and bronchial hyperresponsiveness in athletes are outlined. Criteria are given for the diagnosis of asthma and exercise induced asthma in the athlete. Conclusions: The prevalence of asthma and bronchial hyperresponsiveness is markedly increased in athletes, especially within endurance sports. Environmental factors often contribute. Recommendations for the diagnosis of asthma in athletes are outlined.